LEARNING MODEL FOR IMPROVING THE EFFECTIVENESS OF STUDENTS’ LEARNING PERFORMANCE IN LESSONS - Shayner, Anna; Shvay, Roksolyana; Rarot, Halina (Journal of Education Culture and Society, 2020)
Purpose. The objective of this study is to suggest and demonstrate the feasibility of a new learning model and compare learning outcomes due to the traditional and developed learning models. Methods. The advantages of the developed model are proved in accordance with statistical processing of the pedagogical experiment results using Statistica. The experiment involves 786 students who are aged 13-14 and study in grades 7-8. The time parameters of the duration of individual elements of the lesson in the traditional learning model are consistent with the methodological literature (Horonovska & Samsonova, 1985; Sadovyi, Vovkotrub, & Tryfonova, 2013). Results. The methodology of selecting generic content units (GCUs) from the subject content and their division into theoretical (TCUs) and experimental (ECUs) content units is elaborated. The total time of all TCUs gives the duration of the teaching process while the time of all ECUs is the duration of the knowledge process acquisition, and the time of GCUs is the duration of the learning process. The result of the GCUs presentation offers two learning models: traditional (sequential) and developed (parallel) ones. Conclusions. The broad implication of the present research is that the developed "parallel" model allows using the time effectively for practical students’ research work at physics lessons, and enables to give better learning outcomes, use individual and group forms of learning with observance of individualization and differentiation learning principle. This model assists in building pedagogical teaching technologies for different subjects.